Generation of copper nanoparticles induced by fs-laser irradiation in borosilicate glass - Almeida, J. M.P.; De Boni, L.; Avansi, W. [UNESP]; Ribeiro, C.; Longo, E. [UNESP]; Hernandes, A. C.; Mendonca, C. R. (Optica Publishing Group, 2012)
Glasses containing metallic nanoparticles are promising materials for technological applications in optics and photonics. Although several methods are available to generate nanoparticles in glass, only femtosecond lasers allow controlling it three-dimensionally. In this direction, the present work investigates the generation of copper nanoparticles on the surface and in the bulk of a borosilicate glass by fslaser irradiation. We verified the formation of copper nanoparticles, after heat treatment, by UV-Vis absorption, transmission electron microscopy and electron diffraction. A preferential growth of copper nanoparticles was observed in the bottom of the irradiated region, which was attributed to self-focusing in the glass © 2012 Optical Society of America.